MANAJEMEN PEMBELAJARAN FIQIH MAWARIS DALAM KITAB MABAHITS FII ILMI MAWARITS UNTUK MEMBENTUK KARAKTER ADIL DI MAHAD ALY BAHASA ARAB DAN PENDIDIKAN ISLAM SURAKARTA - Abasir, Muttorik Alil; Daliman, D; Hidayat, Febryan (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Learning management in science is a series of managemenent processes and leadership efforrts form teachers in planning, implementing, assessing, or evaluating a lesson in order to achieve predetermined goals. The focus of the research is to find out how the management learning the science of roses in the book Mabahits fii ilmi mawarits is to form a fair character for student at Mahad Aly Arabic and Islamic Education in Surakarta. This research uses a descriptive-qualitative approach. Collecting data using observation techniques, interviews, an documentation. The data analysis technique uses descriptive-qualitative with an interactive model by Miles Huberman and Saldana with step: 1) Condersing data 2) Presentation of data 3) Drawing conclusions. The data validity method uses source triangulation and technique triangulation. Learning planning can be carried out by all teachers, while implementation is generally carried out by full-fledged science teachers, and evaluation is also carried out in various ways to obtain maximum result.